Diagnosis of Pulmonary Tuberculosis by Xpert MTB/RIF Assay Using Gastric Aspirate in Children with Pneumonic Consolidation - Khanam, Morsheda; Rahat, Farhana; Hossain, Belayet; Abiduzzaman, Mf; Ghosh, Nobo Krishana (Bangladesh Journal of Child Health, 2024)
Background: In Bangladesh, there is increased evidence of TB-associated pneumonia in children are currently missed or diagnosed too late resulting in deterioration of condition. The objective of this study was to detect the frequency of pulmonary TB in children presented with pneumonic consolidation by Xpert MTB/RIF assay using gastric aspirate. Materials & Methods: This was a prospective observational study. Admitted children from 6 months to 14 years old from January to December 2020 with clinical features consistent with pneumonia and radiographically confirmed consolidations were enrolled in this study. MT and Xpert MTB/RIF assay using gastric aspirates were done in all cases. Data regarding frequency of TB, clinical features and lab findings of enrolled patients were collected and analyzed. Results: Total 7/60 (11.67%) enrolled patients, were confirmed as Pulmonary Tuberculosis by Gene Xpert using gastric aspirates. The most common clinical signs were fever and cough in all (100%) patients. Others had chest pain 23(38.33%), breathing difficulty 21(35%), vomiting 17(28.33%). Younger children less than 5 years (P=.045), contact with TB patient (P= .001), long duration of fever (P = .001), presence of severe acute malnutrition (P = .001) high ESR (P= .009), positive MT (P=.017) were associated with positive rate of Xpert MTB/RIF assay in children. Conclusions: Xpert MTB/RIF assay can assist in fast diagnosing childhood pulmonary TB especially in patients with fever more than one week, malnutrition and having contact with TB patient. BANGLADESH J CHILD HEALTH 2022; VOL 46 (2) : 65-70